PENGARUH KUALITAS LAYANAN PENDIDIKAN TERHADAP KEPUASAN MAHASISWA PROGRAM STUDI MANAJEMEN FAKULTAS EKONOMI PADA UNIVERSITAS SWASTA DI BANDAR LAMPUNG - Endang Siswati Prihastuti; Syahril Daud (Academy of Education Journal, 2019)
This study aims to determine the description of the quality of educational services to student satisfaction after attending the educational process, and the results of this study are used to increase student satisfaction in the future. The population of this research is the management study program students at the Faculty of Economics, Private Universities in Bandar Lampung in 2014, 2015 and 2016. Determination of the size of the sample uses the Isaac and Michael tables with a 5% confidence level and determines the sample members with stratified random sampling. The data analysis technique used is Structural Equation Modeling (SEM), an analysis that combines factor analysis approaches, structural models (Structural Model), and path analysis (Path Analysis). The exogenous variable education service quality (X) consists of tangibles, reliability, responsiveness, assurance and empathy. Whereas endogenous variables of satisfaction (Y) are cognition, affective and psychomotor. The results showed that 1) a description of the quality of educational services according to students' perceptions as a whole including good categories.variable service quality Tangible, reliability, empathy, assurance is more important than responsiveness, 2) description of student satisfaction after attending the education process according to overall student perceptions including good categories, 3) quality of education services has a significant effect on student satisfaction, 4) policy implications indicate the need for improvement in terms of; a) cleanliness of the lecture room, b) resolve student complaints, c) handle administration quickly, d) pay attention to a controlled period of education, e) hospitality of employees in providing services.